Port-hinterland concept evolution: A critical review. (June 2020) - Sdoukopoulos, Eleftherios; Boile, Maria
Abstract: Hinterland transport connectivity is being acknowledged as the second most important factor driving port competitiveness after port costs. Deepening the existing understanding on how the port-hinterland concept has evolved over time, as a result of disruptive changes on trade and transport, can provide a solid basis for ports to enhance their hinterland intelligence, and thus devise better informed and more effective hinterland development strategies. The main aim of the paper is therefore to provide a comprehensive and critical review of port-hinterland related research. It starts from early approaches introduced at the beginning of the previous century. It proceeds to the late 1960s, when containerization significantly transformed port-hinterland networks, and continues till today examining contemporary port-hinterland relationships. The latter have driven the transition from distance-decay to more functional approaches for port-hinterland analysis, within which the role of distance still remains valid but valued differently and within a broader context, where a number of additional parameters are also taken into consideration. With hinterland network dynamics playing now a more important role than the individual performance of ports, forward-thinking approaches need to benefit from enhanced extended and regional network intelligence, deepening the understanding and facilitating the timely evaluation of network impacts resulting from new business trends and models, market developments and innovative technology adoption, which are now taking place a lot faster than before. Highlights: Hinterland connectivity is increasingly shaping port competitiveness. The port-hinterland concept has undergone significant reforms over time. Deepening the understanding of its evolution can provide a solid basis for enhancing hinterland intelligence. A transition to more functional approaches for port-hinterland analysis has already been initiated. Forward-thinking approaches need to be more holistic, and better integrate business and market perspectives.